Linear and Nonlinear Relationship Between International Reserves and Economic Growth: Exploring the Relationship Between International Reserves and Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This investigation employs both linear and nonlinear causality tests to probe the nature of theunderlying causal link between the two variables. These findings inform our recommendation to thepolicymakers in the Indian government that they support efforts to develop and recover the oil and gasindustry in order to realize the country's economic growth potential. foreign exchange reserves thatdeveloping countries have amassed. We achieve this by estimating the need for foreign exchangereserves using a panel smooth transition model, which relaxes two limiting hypotheses, homogeneityand time-stability. The central bank of a country is the custodian of the nation's foreign currencyreserves, often known as international reserves (IR).